A Homotopy Perturbation Solution for Solving Highly Nonlinear Fluid Flow Problem Arising in Mechanical Engineering - Khan, Yasir; Akgul, Ali; Faraz, Naeem; İnç, Mustafa; Akgul, Esra Karatas; Baleanu, Dumitru (Amer Inst Physics, 2018)
In this paper, a highly nonlinear equations are treated analytically via homotopy perturbation method for fluid mechanics problem. The non-linear differential equations are transformed to a coupled non-linear ordinary, differential equations via similarity transformations. Graphical results are presented and discussed for various physical parameters.
International Conference of Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 25-30, 2017 -- Thessaloniki, GREECE
Keywords: steady flow; homotopy perturbation method; magneto-hydrodynamics (MHD)